2012
DOI: 10.1017/s0043933912000323
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic fructans and organic acids as feed additives improving mineral availability

Abstract: Mineral availability is one of the most important concerns in poultry nutrition. In modern, high-producing, meat and laying poultry, mineral metabolism disorders often lead to decreased eggshell quality and osteoporosis in laying hens and bone weakness in broiler chickens. This has negative effects not only on the economic profitability of production but also on the welfare of the birds. The article discusses the results of studies on the effect of chosen feed additives, namely organic acids and prebiotic fruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 75 publications
0
23
0
3
Order By: Relevance
“…However, the study of dietary supplementation of MCFAs, SCFAs, and their combination had no significant effect on laying performance (22). Swiaatkiewicz et al (18) reported that dietary supplementation of 0.50% VFA (0.20% formic, 0.15% propionic, and 0.15% acetic acid), 0.25% MCFA (0.125% caproic and 0.125% capric acid), and 0.30% SCFA + 0.20% VFA had no effect on laying rate, daily egg mass, egg weight, feed consumption, and feed conversion in the layer hens diet with different levels of calcium and phosphorus. Indeed, VFAs were included in the organic acids that increased egg production in layers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study of dietary supplementation of MCFAs, SCFAs, and their combination had no significant effect on laying performance (22). Swiaatkiewicz et al (18) reported that dietary supplementation of 0.50% VFA (0.20% formic, 0.15% propionic, and 0.15% acetic acid), 0.25% MCFA (0.125% caproic and 0.125% capric acid), and 0.30% SCFA + 0.20% VFA had no effect on laying rate, daily egg mass, egg weight, feed consumption, and feed conversion in the layer hens diet with different levels of calcium and phosphorus. Indeed, VFAs were included in the organic acids that increased egg production in layers.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that fish fed 10 g NaDF kg −1 diet had higher serum calcium and inorganic phosphorous concentrations. The results of several studies in chicken showed that the solubility and digestibility of dietary minerals increases by dietary OA as a consequence of reducing intestinal pH that increases the activity of digestive enzymes and modifies intestinal microflora, which eventually enhances their absorption by acidic anion complexes of OA with minerals (Abdel‐Fattah, El‐Sanhoury, El‐Mednay, & Abdel‐Azeem, ; Edwards & Baker, ; Swiatkiewicz & Arczewska‐Wlosek, ).…”
Section: Discussionmentioning
confidence: 99%
“…In animal production, it is known that acidification of gastric contents with organic acids improves the utilization of dietary nutrients by improving the functions of proteolytic enzymes, promoting digestion of protein and amino acids (Partanen et al . ) and the availability of minerals (Swiatkiewicz & Arczewska‐Wlosek ). However, in cats, the absence of changes in nutrient utilization by adding the acidifying agent may be because of an insufficient quantity of microorganisms capable of causing gastrointestinal infection or increased production of hydrochloric acid in the stomach, which shows that correction of the diet with an acidifier may not be required.…”
Section: Discussionmentioning
confidence: 99%